Identifying ULF Wave Eigenfrequencies in SuperDARN Backscatter Using a Lomb‐Scargle Cross‐Phase Analysis. Issue 2 (11th February 2019) - Wharton, S. J.; Wright, D. M.; Yeoman, T. K.; Reimer, A. S.
Abstract: The eigenfrequencies of standing Alfvén waves on closed magnetospheric field lines can be estimated using the cross‐phase technique. These eigenfrequencies can be used to monitor the plasma mass density distribution along the field line. So far, this has only been applied to ground‐based magnetometer data. The Super Dual Auroral Radar Network (SuperDARN) radars offer some benefits over magnetometers. They provide greater spatial resolution and coverage, as well as direct sensing above the E region ionosphere, which screens ultralow frequency (ULF) waves from the ground. However, there are significant data quality issues. These include the uncertain origin of radar backscatter, uneven sampling of data due to data gaps, and inaccurate fitting to the autocorrelation functions. Artificial backscatter from an ionospheric heater has been used to remove the uncertainty in backscatter location. We have developed a Lomb‐Scargle cross‐phase analysis for application to discontinuous radar data. The First Principles Fitting Methodology has been used to improve the fitted data products derived from the autocorrelation functions. Using these techniques, we have shown that it is possible to measure eigenfrequencies with SuperDARN data, and we have verified an example using ground‐based magnetometer data. Finally, we have demonstrated that the eigenfrequency signature in this example was caused by a broadband source of energy. Key Points: Used SuperDARN to estimate magnetospheric ULF eigenfrequencies with the cross‐phase technique Lomb‐Scargle and lmfit2 applied to artificially induced and natural backscatter Confirmed a local eigenfrequency signature seen in SuperDARN was also observed in ground magnetometer data